Drosophila Neurexin IV stabilizes neuron-glia interactions at the CNS midline by binding to Wrapper. - Stork, T.; Thomas, S.; Rodrigues, F.; Silies, M.; Naffin, E.; Wenderdel, S.; Klämbt, C. (Development, 2009)
Ensheathment of axons by glial membranes is a key feature of complex nervous systems ensuring the separation of single axons or axonal fascicles. Nevertheless, the molecules that mediate the recognition and specific adhesion of glial and axonal membranes are largely unknown. We use the Drosophila midline of the embryonic central nervous system as a model to investigate these neuron glia interactions. During development, the midline glial cells acquire close contact to commissural axons and eventually extend processes into the commissures to wrap individual axon fascicles. Here, we show that this wrapping of axons depends on the interaction of the neuronal transmembrane protein Neurexin IV with the glial Ig-domain protein Wrapper. Although Neurexin IV has been previously described to be an essential component of epithelial septate junctions (SJ), we show that its function in mediating glial wrapping at the CNS midline is independent of SJ formation. Moreover, differential splicing generates two different Neurexin IV isoforms. One mRNA is enriched in septate junction-forming tissues, whereas the other mRNA is expressed by neurons and recruited to the midline by Wrapper. Although both Neurexin IV isoforms are able to bind Wrapper, the neuronal isoform has a higher affinity for Wrapper. We conclude that Neurexin IV can mediate different adhesive cell-cell contacts depending on the isoforms expressed and the context of its interaction partners.